PEMBELAJARAN ORANG DEWASA BERBASIS ANDRAGOGI: TINJAUAN TEORI - Sumiyarno Sumiyarno (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
The education level of many adult people generally is low. The result of examining towards a considerable body of literature on the concepts of andragogy shows that now many of practices of adult education and training have been conducted by using a pedagogical approach. Their practices are not effective since the orientation toward learning for adult people is one of subject-centeredness. Consequently, the education and training for adults should be promoted by using andragogybased learning and the orientation toward learning is one of problem-centeredness.